БОЖЕСТВЕННЫЕ РЕЛИГИИ И РЕЛИГИОЗНЫЕ ЗАКОНЫ С ТОЧКИ ЗРЕНИЯ КОРАНА (Вестник КазНУ. Серия Востоковедения, 2016)
Құранның басқа да әлемдік діндер мен шариғатқақатынасын діни тұрғыдан Ислам ойшылдары әр түрлітүсіндіреді. Ең бір назар аударарлық, қызығушылық ту-дырарлық мәселе діни заңдарды жою, өзгерту. Мақа-лада Құран тұрғысынан келгендегі құдайлық дін жәнедіни заңдар туралы жазылған.The discussion of the status of divine religions and itsreligions is plausible, especially, from the Quran's andMoslem's points of view. The question is whether Islam in ageneral view of religions and or the view of religions and orthe view of religions of divine religions has been nullified?Basically, nullification in religions is significant.Religious jurisprudence and words are two parts ofreligions and the question is how are they together and alsowithout each other. There is an attempt in this article toanswer these questions.
Keywords: РЕЛИГИИ И ЗАКОНЫ С ТОЧКИ ЗРЕНИЯ КОРАНА